Analysis of Da'wah Science and Islam in Educating Ummah by Dr. Zakir Naik through Islamic Communication in Internet Videos - Anwar, Ikbalul (International Journal of Education, Culture, and Society, 2023)
Internet video is a new form of media that allows us to study the movement of narratives. Lectures discussing Islam and science often appear in this video. One of the most popular speakers in this material is Dr. Zakir Naik, a Muslim preacher from India. Dr Zakir Naik's lectures often interpret certain modern scientific discoveries to prove the divine origin of the Qur'an, Dr. Zakir Naik also uses material from the lecture "Qurʾān and Modern Science" in other lectures. He has included material i ʿ jāz ʿilmī similarly structured under various titles. This focus on iʿjāz creates a space where Muslims and others use videos and clips of Naik, sometimes for their own purposes. More research needs to be done, but Dr. Zakir Naik's video curation has the opposite point of view in the viewing and dissemination of the criticism video. Copying a video to a new user's "channel" opens it up to a new deployment network, new opportunities for discussion via comments and "likes", and new framing with changes in title, description, tags, and subtitles. The same goes for video criticism, which also generates backlash. As is common in fan-based media, the line between professional performance and amateur commentary quickly breaks down.